FEATURES OF INFLUENCE OF INTERNET MEDIA ON THE INFORMATIONAL ECONOMY - Ноздріна, Лариса; Височанська, Каріна (Socio-economic relations in the digital society, 2019)
The rapid development of information and telecommunication technologies (ICTs) nowadays has leds toan increase in the role of information and knowledge in all spheres of human activity was described in this article. It is noted that in the modern information economy information is commodity products that due to the leading role of ICT influences the country᾿s economic development. It is analyzed that information activity in society belongs to the «knowledge industry», which also covers sectors such as: 1) information technologies and services; 2) education; 3) scientific research; 4) development; 5) the media (whicharerepresentedinparticularonthe Internet).The modern tendencies of the information economy development with the help of project᾿s realization of the research of influence of the Internet mass-medias one conomics development in Ukraine was studied. Using the Google Form cloudservice, a survey on Internet mediausers, that was based on comparatively modern state of Ukrainian- and Polish-languagemarkets, was conducted. The results of the project identified: the most informative channels of online resources in the Ukrainian and Polish markets; the using of Internet sources in conducting business activities; dependencies between
Keywords: information economy; industry of knowledge; mass media; Internet media; cloud service; questionnaires; Ukrainian and Polish Internet media